Performance of CRA-40 reanalysis in representing the Antarctic winter stratospheric circulation: a comparison with ERA-5 and MERRA-2 - ZiXu Wang; JingGao Hu; Jing-Jia Luo; Jian Rao; ZongZe Li; LiuChi Yan (Earth and Planetary Physics)
This paper evaluates a representation of winter stratospheric circulation in the Antarctic that is based on CRA-40, a 40-year global reanalysis dataset released by the China Meteorological Administration, and compares it with representations based on two other state-of-the-art reanalysis datasets: the fifth-generation atmospheric reanalysis provided by the European Centre for Medium-Range Weather Forecasts (ERA-5) and the Modern-Era Retrospective analysis for Research and Applications, version 2 (MERRA-2). In terms of climatology, we find that CRA-40 portrays a stronger and colder polar vortex in the middle and lower stratosphere than ERA-5, but a weaker and warmer one than MERRA-2. However, disagreement among the three reanalyses is confined mainly to the period before 1999, and is largely reduced after that time. On the interannual timescale, portrayals of the intensity and area of the 10-hPa polar vortex are quite consistent among the three reanalyses, with correlation coefficients greater than 0.9 between each pair of reanalyses. In addition, the central dates of most sudden stratospheric deceleration (SSD) events at 10 hPa in the three reanalyses differ by less than one day, indicating that CRA-40 is also highly consistent with the other two reanalysis datasets regarding daily evolution. Our analyses suggest that CRA-40 performs comparably to ERA-5 and MERRA-2 in characterizing winter circulation in the Antarctic middle and lower stratosphere.